2012
DOI: 10.1111/j.1523-5378.2012.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher Motility Enhances Bacterial Density and Inflammatory Response in Dyspeptic Patients Infected with Helicobacter pylori

Abstract: Background Motility mediated by the flagella of Helicobacter pylori is important for the cells to move toward the gastric mucus in niches adjacent to the epithelium; then, H. pylori uses the adhesin SabA to interact with sialyl‐Lex on inflammatory host cells for persistent infection. Here, we reveal the clinical association of bacterial motility, SabA expression, and pathological outcomes. Methods Ninety‐six clinical isolates were screened for bacterial motility, and the expression of SabA of each isolate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…In E. coli and Pseudomonas aeruginosa, flagellin and/or the distally located flagellar cap protein have been reported to function as adhesins [25]. The combination of virulence factor expression and higher motility of H. pylori leads to synergistic effects on gastric pathology [8]. This study, showing a greater prevalence of afa and ompT genes in the lower-motility E. coli isolates, suggests that more bacterial virulence traits may be necessary for the development of clinical E. coli infections by lower-motility strains.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In E. coli and Pseudomonas aeruginosa, flagellin and/or the distally located flagellar cap protein have been reported to function as adhesins [25]. The combination of virulence factor expression and higher motility of H. pylori leads to synergistic effects on gastric pathology [8]. This study, showing a greater prevalence of afa and ompT genes in the lower-motility E. coli isolates, suggests that more bacterial virulence traits may be necessary for the development of clinical E. coli infections by lower-motility strains.…”
Section: Discussionmentioning
confidence: 88%
“…In the pathogenesis of SBP, bacterial translocation from the intestine into the mesenteric lymph nodes, followed by bacteremia and ascitic fluid colonization due to impaired local and systemic immunity, are considered to be two important steps [21,22]. In our previous study, higher H. pylori motility was associated with increased H. pylori density and inflammation severity, and the prevalence rate of gastric atrophy was increased in dyspeptic patients infected with higher-motility strains [8]. We speculate that higher E. coli motility might increase the bacterial density on, and enhance the inflammatory response of, intestinal enterocytes, and contribute to the translocation of E. coli from the intestinal lumen and development of SBP in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As already mentioned in this chapter (see section 1.2.1 of this chapter) motility is a long known virulence-related trait [46], with lower-motility associated reduced inflammation levels [47] and with non-motile strains unable to establish a robust infection [42,45,46]. Moreover, it was more recently shown that higher motility enhances H. pylori density and inflammatory response in dyspeptic patients [130].…”
Section: Molecular Profile Of Ulcerogenic Paediatric H Pylori Strainsmentioning
confidence: 99%